Analysis of the Effect of Understanding Taxation and Tax Rates on the Compliance of MSME Taxpayers in Simpang Tanjung - Ester Vanessa Lumban Tobing; Cindi Aulia Wanda; Siti Nazla Hayati; Desi Triana Munthe (International Journal of Society and Law, 2024)
The purpose of this study is to determine the effect of understanding taxation, tax rates on taxpayer compliance with MSMEs. This research uses the tax object of MSMEs Simpang Tanjung. The sample in this study consisted of 10 respondents of MSME taxpayers who had an annual sales turnover below Rp 50,000,000,000 in the Simpang Tanjung area. This research is qualitative research. The method of data collection is by field study. Based on the results of research and discussions that have been carried out, it can be concluded that there is an influence of taxation understanding owned by taxpayers on the compliance of MSME Taxpayers in Simpang Tanjung, tax rates affect the compliance of MSME Taxpayers in Simpang Tanjung.